2018
DOI: 10.1021/acs.energyfuels.8b01301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fuels and Oxygen Indices on the Morphology of Soot Generated in Laminar Coflow Diffusion Flames

Abstract: The morphological characteristics of soot are of primary importance to quantify its effect on climate forcing and human health and also to interpret the signals acquired in optically based soot diagnostics. In the present study, the morphology of soot particles produced in laminar coflow diffusion flames was investigated under different fuel and oxidizer conditions. Particles were sampled thermophoretically at the centerline at different heights above the burner in laminar diffusion flames of three common fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 67 publications
(145 reference statements)
1
7
0
Order By: Relevance
“…Wentzel et al (2003) found values between 0.1 and 0.29 for soot aggregates from diesel emissions. As another example, Cortés et al (2018) reported values of 0.04 ≤ Cov ≤ 0.18 when using TEM to study soot aggregates generated in co-flow diffusion flames using different fuels (ethylene, propane and butane), which is in good agreement with the values (0.11-0.17) of soot aggregates derived from diffusion flames reported in . The overlap of primary particles in soot aggregates has gained attention because it impacts the radiative properties of the aggregates (e.g.…”
Section: Overlap Between Primary Particlessupporting
confidence: 81%
See 2 more Smart Citations
“…Wentzel et al (2003) found values between 0.1 and 0.29 for soot aggregates from diesel emissions. As another example, Cortés et al (2018) reported values of 0.04 ≤ Cov ≤ 0.18 when using TEM to study soot aggregates generated in co-flow diffusion flames using different fuels (ethylene, propane and butane), which is in good agreement with the values (0.11-0.17) of soot aggregates derived from diffusion flames reported in . The overlap of primary particles in soot aggregates has gained attention because it impacts the radiative properties of the aggregates (e.g.…”
Section: Overlap Between Primary Particlessupporting
confidence: 81%
“…Delhaye et al, 2017;Liati et al, 2014Liati et al, , 2019Marhaba et al, 2019;Smekens et al, 2005), and commercial carbon blacks and/or soot generated from controlled flames in the laboratory (e.g. Clague et al, 1999;Cortés et al, 2018;Ferraro et al, 2016;Megaridis and Dobbins, 1990;Ouf et al, 2016Ouf et al, , 2019. For instance, Liati et al (2014) used TEM to investigate the size of primary particles of a turbofan engine (type CFM 56-7B26/3), frequently used in Boeing 737 aircrafts that was operated with standard Jet A-1 fuel.…”
Section: Primary Particle Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Both intrusive and non-intrusive diagnostics have been used for many years in laboratory flames at atmospheric pressure to study soot (Sorensen et al, 1992, Koylu, 1997, Hu et al, 2003, Fang et al, 1998, De Iuliis et al, 1998a, De Iuliis et al, 2011, Cortés et al, 2018, Ferraro et al, 2016. Laser diagnostics are favored for soot studies in flames due to their non-perturbing nature.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen enrichment, which may be used to increase the peak-flame temperature, decrease flue gas losses, or reduce equipment size, is applied in some industrial applications (e.g., glass manufacturing and aluminum recycling) and in oxy-fuel combustion for carbon capture. Several studies have investigated oxygen-enriched combustion for co-flowing diffusion flames experimentally [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], and many have noted a significant increase in soot formation when the oxygen content in the oxidizer was increased (due to higher temperatures and reaction rates). As for the impact of pressure on soot formation in laminar flames, the soot volume fraction appears to scale in proportion to the total pressure in terms of a power-law, i.e., ∝ P n .…”
Section: Introductionmentioning
confidence: 99%